1970
DOI: 10.3126/kumj.v7i2.2700
|View full text |Cite
|
Sign up to set email alerts
|

Tearfilm immunoglobulin E (IgE) level in vernal keratoconjunctivitis by ELISA

Abstract: Background: Vernal keratoconjunctivitis (VKC) is recurrent chronic allergic conjunctivitis occurring in the prepubertal age-group with secondary involvement of the cornea and is self-limiting in character. The disease is prevalent worldwide but it shows predominance in the areas with dry and warm climate including the South Asia. VKC represents about 3% of the serious ophthalmic disease in some parts of the world where the prevalence is rate is high.Type I hypersensitivity reaction which is IgE-dependent and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Mumcuoglu et al ( 1988 ) sampled serum and tear for measuring total and specific IgE to 10 inhalant allergens and reported a positive test in 42% of patients and to house dust mites only. Pokharel et al ( 2009 ) reported that mean total tear IgE was higher in patients with VKC than in controls, but this difference did not reach statistical significance. Pucci et al ( 2003 ) reported that 45% of VKC patients had a positive skin prick test with house dust mites being the most prevalent allergen, and that patients had significantly higher serum total IgE and peripheral blood eosinophils compared to controls.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Mumcuoglu et al ( 1988 ) sampled serum and tear for measuring total and specific IgE to 10 inhalant allergens and reported a positive test in 42% of patients and to house dust mites only. Pokharel et al ( 2009 ) reported that mean total tear IgE was higher in patients with VKC than in controls, but this difference did not reach statistical significance. Pucci et al ( 2003 ) reported that 45% of VKC patients had a positive skin prick test with house dust mites being the most prevalent allergen, and that patients had significantly higher serum total IgE and peripheral blood eosinophils compared to controls.…”
Section: Resultsmentioning
confidence: 97%
“…High levels of total IgE in tears are associated with allergic conjunctivitis (Monzón et al, 2009 ; Mumcuoglu et al, 1988 ; Pokharel et al, 2009 ). Patients with VKC are reported to have specific IgE in tears for dust mites, pollen (grass, tree), animal (cat), and food allergies (Leonardi et al, 2015 ; Mumcuoglu et al, 1988 ; Tuft et al, 1989 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…satu hal terpenting untuk mendiagnosa konjungtivitis alergi (6). Penelitian yang dilakukan oleh Nomura dan METODE Takamura menggunakan ELISA, menyebutkan bahwa Penelitian dilakukan dengan desain pre and post clinical didapatkan peningkatan kadar IgE air mata pada trial pada 32 penderita alergi okuli yang dibagi menjadi penderita VKC, SAC dan PAC (7,8).…”
Section: Pendahuluanunclassified
“…(4) The exact mechanism of vernal keratoconjunctivitis is not fully understood at the time being, (5) but there is a possibility of type I and IV hypersensitivity reactions involvement with vasoactive mediators release. (6)(7) There are three types of vernal keratoconjunctivitis, palpebral, limbal, and mixed, Fig. 1a, b, and c respectively.…”
Section: Introductionmentioning
confidence: 99%